Legal Regulation of Public Governance in Finland – an Illusion of Predictable Public Administration? - Mäntylä, Niina; Perttola, Laura; Siikavirta, Kristian (Socialiniai tyrimai, 2015)
Legal coherence and predictable decision-making are the cornerstones of Finnish administrative law. The aim of this research is to analyze the factors that make administrative decisions unpredictable in Finland today. Why is the challenge so significant for the authorities? The factor analysis revealed six main features affecting predictability in the legal regulation of Finnish public governance: the increasing use of soft law, the devolution of government, deregulation, the changing role of the individual, the blurring of the division between the public and the private sector and the influence of international and EU-law.